Counseling Multicultural Student-Athletes: An Examination of Barriers - Coleman, Victoria D.; Barker, Shirl A. (My University, 1992)
This article identified some barriers to the academic and career development of multicultural student-athletes. Barriers may have an adverse effect on the academic progress and athletic performance of this population. Consequently, it is imperative that academic advisors and professionals in counseling and development become aware of the obstacles that might be encountered as student-athletes from different backgrounds seek to maximize their academic and athletic potential. These barriers are discussed, along with implications for professionals who work with this population.
Keywords: race; demographics; at-risk